Neuromyelitis Optica Spectrum Disorders - from pathophysiology to treatment - Jessica Adriana Kałuża; Oliwia Bochenek; Aleksandra Nowak; Mateusz Koper; Adrian Konaszczuk; Klaudia Ratyna; Oliwia Kozyra; Zofia Szypuła; Katarzyna Paluch; Małgorzata Skarbek (Nicolaus Copernicus University in Toruń, 2024)
Neuromyelitis optica spectrum disorders (NMOSD) are a group of autoimmune diseases characterized by severe, inflammatory attacks predominantly affecting the optic nerves and spinal cord and central nervous system. NMOSD presents with clinical features such as optic neuritis, acute myelitis, and area postrema syndrome, making it a challenging condition to diagnose due to its varied clinical manifestations. Untreated, approximately 50% of NMOSD patients will be wheelchair users and blind, and a third will have died within 5 years of their first attack. Historically considered a variant of multiple sclerosis, NMOSD is now recognized as a distinct entity, largely due to the discovery of the pathogenic role of aquaporin-4 (AQP4) antibodies. Approximately 75% of patients have antibodies against aquaporin-4, a water channel expressed on astrocytes. These antibodies target astrocytes, leading to complement activation, inflammation, and subsequent damage to the central nervous system. Relapses are treated with high-dose steroids and plasma exchanges to prevent residual disability. Advances in understanding the pathophysiology of NMOSD have paved the way for targeted therapies, including monoclonal antibodies that inhibit complement activation, B-cell depletion strategies, and interventions targeting interleukin-6 signaling. Four preventive immunotherapies have now been approved for AQP4-IgG-positive NMOSD in many regions of the world: eculizumab, ravulizumab inebilizumab, and satralizumab. These treatments have significantly improved disease outcomes, offering hope for better management of NMOSD, although challenges remain in early diagnosis, treatment accessibility, and preventing relapses. Further research is essential to refine therapeutic approaches and explore novel targets to enhance patient care.